2010
DOI: 10.1177/159101991001600203
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment Accounts for a Change in Brain Arteriovenous Malformation Natural History Risk

Abstract: This study estimated the risk and rates of intracranial hemorrhage (ICH) in patients harboring brain arteriovenous malformation (BAVM) after endovascular embolization. One hundred and forty-four consecutive patients with BAVM treated with endovascular embolization between 1998 and 2003 were retrospectively reviewed. The risk of ICH subsequent to endovascular embolization was studied using Kaplan-Meier curves. We reviewed 144 patients with BAVM treated with endovascular embolization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…In three dimensions, Eq. (3) can be generalized to (6) where the permeability k is a general secondorder tensor. The terms v and ∇p are Darcy conditions and filled the directly dependent nidus compartment antegradely and later retrogradely until it flowed to the tip of the microcatheter.…”
Section: Resultsmentioning
confidence: 99%
“…In three dimensions, Eq. (3) can be generalized to (6) where the permeability k is a general secondorder tensor. The terms v and ∇p are Darcy conditions and filled the directly dependent nidus compartment antegradely and later retrogradely until it flowed to the tip of the microcatheter.…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative intravascular embolization may reduce the risk of bleeding in surgery, but endovascular embolization likely cause ischemic or hemorrhagic complications. 16,17 If the fetus is mature, hemorrhagic AVM should be resected at early postpartum. 14 Robinson et al reported that mothers with hemorrhagic AVM were treated by neurosurgical operations, in which there were no mother deaths, 26% fetal mortality, and maternal mortality was 10% in a conservative treatment group.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Preoperative intravascular embolization may reduce the risk of bleeding in surgery, but endovascular embolization is likely to cause ischemic or hemorrhagic complications. 16,17 If the fetus is mature, a hemorrhagic AVM should be resected at an early stage postpartum. 14 Robinson et al reported that when mothers with hemorrhagic AVM were treated by neurosurgical operation, there were no deaths among the mothers, fetal mortality was 26%, and maternal mortality was 10% in a conservative treatment group.…”
Section: Neurosurgical Treatment Of Cerebral Avm In Pregnancymentioning
confidence: 99%